A study on wastewater minimazation techniques for textile mills & washing companies - Singson, Ma. Margarita Y.
Textile manufacturing involves three main process namely: spinning, weaving, and finishing. This study on wastewater minimization techniques for textile mills and washing companies will focus on ways of decreasing the formation of wastewater generated from the fishing and washing processes alone since virtually all wastewater is created in the said processes. Wastewater is mainly generated by scouring, desizing, dyeing, mercerizing, bleaching, printing, and other final finishing operations which is quite similar to the washing processes in apparel. Variability in composition is a marked feature of most textile effluents. Unless coming from sources with the same nature, wide variations in composition, temperature flow, and pH value are prevalent. The main components of wastewater include natural impurities extracted from the fiber as well as process chemicals which are removed from the cloth and discarded as wastes. Textile wastes are generally colored, highly alkaline, high in BOD and suspended solids, and high in temperature. These characteristics are the basis of the standards set by the LLDA for wastewater discharge into streams. A case study conducted on the present wastewater treatment practices of the representative textile mill and the washing companies revealed that the two industries follow basically the same wastewater treatment process. Physico-chemical process and an activated sludge system though can only be effective through the use of modern pollution control facilities which would entail a great deal of financial resource. Resorting to waste management options that focus on volume and strength reduction and recycling processes or on low-waste technologies should therefore be seriously considered. At present, the programme of action must be corrective in nature rather than preventive. The most practical thing to do is to address the problem at hand.